Vascular Transdifferentiation in the CNS: A Focus on Neural and Glioblastoma Stem-Like Cells - Sophie Guelfi; Hugues Duffau; Luc Bauchet; Bernard Rothhut; Jean-Philippe Hugnot (Stem Cells International)
Glioblastomas are devastating and extensively vascularized brain tumors from which glioblastoma stem-like cells (GSCs) have been isolated by many groups. These cells have a high tumorigenic potential and the capacity to generate heterogeneous phenotypes. There is growing evidence to support the possibility that these cells are derived from the accumulation of mutations in adult neural stem cells (NSCs) as well as in oligodendrocyte progenitors. It was recently reported that GSCs could transdifferentiate into endothelial-like and pericyte-like cells both in vitro and in vivo, notably under the influence of Notch and TGFβ signaling pathways. Vascular cells derived from GBM cells were also observed directly in patient samples. These results could lead to new directions for designing original therapeutic approaches against GBM neovascularization but this specific reprogramming requires further molecular investigations. Transdifferentiation of nontumoral neural stem cells into vascular cells has also been described and conversely vascular cells may generate neural stem cells. In this review, we present and discuss these recent data. As some of them appear controversial, further validation will be needed using new technical approaches such as high throughput profiling and functional analyses to avoid experimental pitfalls and misinterpretations.